Modelling and preliminary results of a tri-ellipsoid unmanned autonomous airship. (2016) - Zheng, Enhao; Mai, Jingeng
Unmanned autonomous airship has its own advantages over other aerial vehicles in near-ground surveillance and rescue tasks. In this study, we present a novel designed unmanned autonomous blimp. We built the dynamic model of the tri-ellipsoid blimp then we designed an anti-wind controller based on the model. We also implemented the prototype which included the tri-ellipsoid blimp body, the flying control system and the ground communication station. We carried out field experiments including payload experiment, remote control experiment and automatic flying experiment to validate the system. Experimental results demonstrate that the proposed blimp is a potential tool in accomplishing tasks of near-ground search with large payloads.